Increasing incidence rate of breast cancer in cystic fibrosis - relationship between pathogenesis, oncogenesis and prediction of the treatment effect in the context of worse clinical outcome and prognosis of cystic fibrosis due to estrogens - Stastna, Nela; Brat, Kristian; Homola, Lukas; Os, Audun; Brancikova, Dagmar (Orphanet journal of rare diseases, 2023)
Cystic fibrosis (CF) is the most common genetic disease in the Caucasion population. Thanks to the CFTR modulators therapy, life expectancy will significantly improve. New therapeutic challenges can be expected, including diseases associated with ageing and higher incidence of cancer, as evidenced by recent epidemiological studies. The increasing incidence of tumors includes also breast cancer. The risk of breast cancer is higher in CF patients compared to the general population. Sex hormones, especially estrogens, also affect on the pathophysiology and immunology of the CF. Previous research, has demonstrated unequivocal survival rates for female CF patients compared to their male counterparts. Is demonstrated, that chemotherapy used for breast cancer affects the CFTR channel and CFTR modulator therapy has frequent side effects on breast tissue. In this review, we focus on the effects of female sex hormones on CF disease, pathophysiological relationships between CF and breast cancer, and the impact of antitumor treatment on both, malignant disease and CF. The potential for further investigation is also discussed.
Keywords: Cystic Fibrosis Transmembrane Conductance Regulator; Breast Neoplasms; estrogeny; Incidence; Prognosis; mužské pohlaví; mutace; incidence; Carcinogenesis; Cystic Fibrosis; ženské pohlaví; prognóza; cystická fibróza; protein CFTR; pohlavní steroidní hormony; Humans; Mutation; Estrogens; nádory prsu; Gonadal Steroid Hormones; Female; karcinogeneze; lidé; Male